Evaluation of the Hydrodynamic Impacts of Tidal Turbine Arrays in Jiaozhou Bay - Chao Zhang; Xiuyan Yang; Yuan Jiang; Wei Zhao; Junyu Yu (Journal of Marine Science and Engineering)
In this paper, a hydrodynamic model of Jiaozhou Bay was developed using the Regional Ocean Modeling System and validated against observed tidal levels and current data. The model accurately characterizes the tidal and current features of the region. Based on this model, the spatial and temporal distributions of flow fields and tidal energy resources were analyzed. A 100-turbine tidal power plant was simulated utilizing a momentum-based approach that accounts for resource distribution, bathymetry, topography, and turbine parameters. The resulting hydrodynamic changes, including velocity variations peaking at 0.5 m/s within the turbine deployment zone and tidal level shifts confined to the bay (maximum change in ~10 cm), emphasize the importance of localized environmental assessments. However, the findings also highlight broader considerations for the sustainable development of tidal energy in semi-enclosed bays worldwide, where strategic siting and design can mitigate larger ecological disturbances. These findings may provide a scientific foundation for balancing clean energy extraction with minimal environmental impact, thus contributing to global efforts to develop more resilient and sustainable coastal energy systems.